International Monetary Fund Annual Report 2017 : Promoting Inclusive Growth. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
During the past financial year, the IMF's 189 member countries faced a number of pressing challenges. IMF work on these challenges-slower trade, declining productivity, gender inequality, inclusive growth, and debt management-is a central focus of this 2017 Annual Report.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet